PENYIMPANGAN BUNYI ONOMATOPE: STUDI KASUS FONOLOGI DALAM LAGU ANAK-ANAK BERBAHASA INGGRIS - Muhammad Wildan Febrian; Dila Fadlilah Syahlan; Anindya Qinthara; Kezia Elizabeth Debora; Odelia Carmelita (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2022)
This study aims to show the deviation of onomatopoeic sounds pronounced by children aged 4-5 years with their main language other than English. In this study, the onomatopoeic sounds used as data sources were the sounds of “quack,” “oink,” “swish,” “choo-choo” and “moo'' which were found in English children's songs. The data collection technique was carried out by making an audio recording containing the onomatopoeic pronunciation by the research objects. In addition, a questionnaire was given to the parents/guardians of the research objects containing questions regarding the background of the research objects. By using descriptive qualitative research methods, the researchers found several onomatopoeic sound deviations, including non-palatalisation, apocope, raising vocal, lowering vocal, etc. Keywords: English language, children’s songs, Onomatopoeia, Phonology